A construction of Böttcher coordinates for holomorphic skew products. (18th June 2019) - Ueno, Kohei
Abstract: Let be a holomorphic skew product with a superattracting fixed point at the origin. Under one or two assumptions, we prove that f   is conjugate to a monomial map on an invariant open set whose closure contains the origin. The monomial map and the open set are determined by the degree of p   and the Newton polygon of q .